A Glimpse in the Future of Malignant Mesothelioma Treatment - Pezzicoli, Gaetano; Rizzo, Mimma; Perrone, Martina; Minei, Silvia; Mutti, Luciano; Porta, Camillo (Frontiers in Pharmacology, 2021)
Malignant mesothelioma (MMe) is a rare neoplasm with few therapeutic options available. The landscape of effective therapy for this disease remained unchanged in the last two decades. Recently, however, the introduction of Immune Checkpoint Inhibitors (ICIs) led to small, but nevertheless, promising improvements. However, many efforts are still needed to radically improve the prognosis of MMe. In this review, we analyze all those therapeutic strategies for MMe that are still in a preclinical or early clinical phase of development. In particular, we focus on novel antiangiogenic drugs and their possible combination with immunotherapy. Furthermore, we describe also more complex strategies such as microRNA-loaded vectors, oncolytic viruses, and engineered lymphocytes.